Correction to: Health Outcomes of Medication Nonadherence among Older Adults with Chronic Illnesses at an Outpatient Clinic of a Tertiary Care Hospital in Thailand (Journal of the Medical Association of Thailand, 2024)
The author has informed the editor to correct the DOI number in the article as follow: Incorrect DOI number in the article: doi.org/10.35755/jmedassocthai.2021.S04.00051 Correct DOI number doi.org/10.35755/jmedassocthai.2021.S04.00052